REFLECTION OF NORMS AND VALUES IN ENGLISH COMPARISONS WITH THE FLORA COMPONENT (TAMADDUN NURI JURNALI, 2025)
Language is a reflection of culture, its norms, values ​​and mentality. One of the most expressive linguistic structures demonstrating national features of language is comparisons. In English, a significant part of comparisons includes the component flora, which indicates a deep connection of native speakers with nature and their cultural ideas about the plant world. This article examines English comparisons with the component flora that reflect the values, stereotypes and norms of English-speaking society.